Borderlines and Beyond: Strengthening Indonesia’s Land Borders Through Global Insights - Kurnia, Lifany Husnul; Yusgiantoro, Purnomo; Rudyansjah, Tony; Madjid, Adnan; Saputro, Guntur Eko (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
Managing border areas shows how serious a country is in maintaining and regulating its territorial boundaries. One sign is the existence of a clear and comprehensive rule of law as a guideline for such management. This research analyzes Indonesia's land border management policy by comparing it to global best practices to formulate a more effective and sustainable strategy. A qualitative approach was taken to examine border management policies in various countries as lessons for Indonesia, by analyzing legal, social, and economic aspects through literature studies. Indonesia's border management shows strengths in law, security and diplomacy, but still faces challenges such as a lack of technological infrastructure. Countries like Poland have successfully tackled the hard-to-reach border in the Białowieża Forest by implementing AI-based smart fences. Indonesia can replicate this approach through digital transformation and the development of technology-based surveillance systems. In addition, improvements in strengthening the legal framework, providing incentives for cross-border economic development, increasing diplomatic engagement, and optimizing security surveillance must also be carried out simultaneously as an integrative effort in managing Indonesia's borders.